REPRESENTASI DESAIN INTERIOR PUSAT KEBUDAYAAN KOREA SELATAN DI JAKARTA UNTUK MENDUKUNG PENDIDIKAN BERKUALITAS : Representation of Interior Design at the South Korean Cultural Center in Jakarta to Support Quality Education - Valencia Natalie Piet; Susy Irma Adisurya; piet, valencia natalie (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
South Korean culture, such as history, K-pop, K-drama, K-beauty, K-food, and so on, has gained the attention of Indonesian people of various communities and ages. Simultaneously with the increasing interest of the Indonesian people in entertainment, beauty, food & beverage, and other sectors from South Korea, the Korean industry in Indonesia is also increasing. The existence of the South Korean Cultural Center is currently still limited to being a Korean language center and does not yet present South Korean history, art, and technology which are of great interest to the Indonesian public today.This study aims to create an interior design concept for the South Korean Cultural Centerthat complies withits vision and mission, create a space and circulation program that suits the activities and behavior of users, and create a green design concept. This study adapts the 4th point of the Sustainable Development Goals regarding the Quality of Education and uses a qualitative descriptive research method.This design carries a concept with the theme